2014
DOI: 10.1117/12.2056810
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterisation of the new CIS115 sensor for JANUS, the high resolution camera on JUICE

Abstract: JUICE, the Jupiter Icy Moon Explorer, is a European Space Agency L-class mission destined for the Jovian system. Due for launch in 2022, it will begin a science phase after its transit to Jupiter that will include detailed investigations of three of the Galilean moons: Ganymede, Callisto and Europa. JUICE will carry payloads to characterise the Jovian environments, divided into in situ, geophysical and remote sensing packages.A key instrument in the remote sensing package is JANUS, an optical camera operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 3 publications
(3 reference statements)
1
18
0
Order By: Relevance
“…The non-linear conversion has been well fitted using a quadratic function, allowing a full well of 3.4 x 10 4 electrons pixel -1 to be measured. The conversion gain measured using the methods described here can be compared to the conversion gain measured using an iron-55 source of 48.3 µV electron -1 [4]. An iron-55 calibration uses manganese K α X-rays (5898 eV) that on average generate approximately 1616 electrons in silicon; therefore the iron-55 technique provides a calibration at a single signal level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-linear conversion has been well fitted using a quadratic function, allowing a full well of 3.4 x 10 4 electrons pixel -1 to be measured. The conversion gain measured using the methods described here can be compared to the conversion gain measured using an iron-55 source of 48.3 µV electron -1 [4]. An iron-55 calibration uses manganese K α X-rays (5898 eV) that on average generate approximately 1616 electrons in silicon; therefore the iron-55 technique provides a calibration at a single signal level.…”
Section: Discussionmentioning
confidence: 99%
“…A previous publication [4] describes the CIS115 architecture in more detail, and presents some initial characterisation results performed at the Open University including a calibration measurement achieved using an iron-55 radiation source. The calibration allows conversion of the sensor output from a voltage into electrons detected at the pixel, but the responsivity must be assumed to be linear with signal level in order to extrapolate the measurement across the full dynamic range of the detector.…”
Section: Janus: An Optical Camera For Observing the Jovian Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the QE of a modern BSI CIS (e.g. e2v Technologies CIS115) 3 and the expected improvements resulting from using thick, fully depleted substrate. For good sensitivity in the red and near-IR, sensors with thicknesses of at least 50 µm are required (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The readout architecture and a Beginning Of Life (BOL) electro-optic performance study of a front-faced sensor has been reported previously [4], including readout noise and iron-55 calibration. A back-thinned CIS115 with e2v's multi-layer astronomy anti-reflection coating has been specified for the flight sensor in JANUS' focal plane to improve quantum efficiency in the range of 400 nm to 900 nm.…”
Section: Introductionmentioning
confidence: 99%